Comparison of bacterial adhesion to dental materials of polyethylene terephthalate (PET) and polymethyl methacrylate (PMMA) using atomic force microscopy and scanning electron microscopy. Issue 6 (15th March 2016) - Fang, Jie; Wang, Chuanyong; Li, Yifei; Zhao, Zhihe; Mei, Li
Summary: The aim of this study was to compare the bacterial adhesion to denture materials of polyethylene terephthalate (PET) and polymethyl methacrylate (PMMA) using atomic force microscopy and scanning electron microscopy. The adhesion forces of living Streptococcus sanguinis and Streptococcus mutans to PET and PMMA were directly measured using atomic force microscopy (AFM) in liquid. Streptococcal biofilms formed on the two material surfaces were investigated and compared using scanning electron microscopy (SEM) and colony‐forming units (CFU) counting. Surface roughness and hydrophobicity of PET and PMMA were also measured. The results showed that PET surfaces were significantly smoother and more hydrophilic than PMMA surfaces both with and without a salivary film (p < 0.01). The adhesion forces of S. sanguinis and S. mutans to PET surfaces were significantly stronger than to PMMA surfaces in the absence of a salivary film (p < 0.01). In the presence of a salivary film, the adhesion forces of both bacterial strains to PET and PMMA were significantly decreased (p < 0.01). The adhesion forces of S. mutans to PET surfaces (0.14 nN) were still significantly stronger than to PMMA surfaces (0.09 nN) (p < 0.01). The biofilm formed on PET surfaces was also significantly denser and more than on PMMA surfaces (p < 0.05). In conclusion, the bacterial adhesion to PMMA was significantly less in comparison with PET. PMMA may be preferable for patients who have poor oral hygiene, caries susceptibility, periodontosis, and halitosis. SCANNING 38:665–670, 2016. © 2016 Wiley Periodicals, Inc.